TIDAK DIBAYARNYA UANG PENGGANTI OLEH TERDAKWA TINDAK PIDANA KORUPSI DI PENGADILAN TIPIKOR KUPANG - Sepriyanto Thobias Tuka (University of Udayana, 2017)
Corruption is an extraordinary crime for causing losses to the state and violate the rights of social and economic communities. Mode used is also increasingly diverse and sophisticated. Corruption has resulted in poverty so that the perpetrators of corruption should be subject to punishment for compensation. Due to corruption that occurred during this time in addition to harming the country also hamper the continuity of national development. Criminal purpose is for the payment of compensation by weighing possible to convict the criminals that they are a deterrent as well in order to restore the state's financial lost due to an act of corruption (refer to Article 18 of Law No. 31 of 1999). The main problem raised in this study is why the failure to apply for compensation to the criminal defendant corruption. The purpose of this study was to determine the cause of the failure to apply for compensation to the criminal defendant corruption. To collect the data required in this study conducted interviews / questionnaires containing gives a list of questions studied in accordance with aspects along with literature. The data obtained in the study processed and analyzed by descriptive qualitative, solving will contain data and documents related to this study. The results of this study are: the judge in his decision not to impose criminal defendant payment of compensation to the corruption because the judges weigh under Article 18 of Law No. 31 of 1999 and one by one element in the provision of primary charges that elements of any person, element unlawfully, the element acts to enrich themselves or someone else or a corporation, or a state financial harm element of the country's economy, the provisions of Article 55 paragraph (1) to-1 of the Criminal Code and the provisions of Article 64 paragraph (1) of the Criminal Code. Korupsi merupakan kejahatan luar biasa karena menyebabkan terjadinya kerugian negara dan melanggar hak-hak sosial dan ekonomi masyarakat. Modus yang digunakan juga semakin beragam dan canggih. Korupsi telah mengakibatkan kemiskinan sehingga pelaku korupsi harus dikenakan pidana pembayaran uang pengganti. Akibat tindak pidana korupsi yang terjadi selama ini selain merugikan negara juga menghambat kelangsungan pembangunan nasional. Tujuan pidana pembayaran uang pengganti adalah untuk memidana dengan seberat mungkin para koruptor agar mereka jera serta dalam rangka mengembalikan keuangan negara yang melayang akibat suatu perbuatan korupsi (menunjuk pada Pasal 18 Undang-Undang Nomor 31 Tahun 1999). Permasalahan pokok yang diangkat pada penelitian ini adalah mengapa tidak diterapkannya pidana pembayaran uang pengganti kepada terdakwa tindak pidana korupsi. Adapun tujuan dari penelitian ini adalah untuk mengetahui penyebab tidak diterapkannya pidana pembayaran uang pengganti kepada terdakwa tindak pidana korupsi. Untuk mengumpulkan data yang dibutuhkan dalam penelitian ini dilakukan wawancara / memberikan kuisioner yang berisi daftar pertanyaan sesuai dengan aspek yang diteliti beserta studi pustaka. Data yang diperoleh dalam penelitian diolah kemudian dianalisis secara deskriptif kualitatif, pemecahan akan berisi data dan dokumen yang berkaitan dengan penelitian ini. Hasil dari penelitian ini antara lain : hakim dalam putusannya tidak menjatuhkan pidana pembayaran uang pengganti kepada terdakwa tindak pidana korupsi karena majelis hakim menimbang berdasarkan Pasal 18 Undang-Undang Nomor 31 Tahun 1999 satu per satu unsur dan ketentuan dalam dakwaan primer yaitu unsur setiap orang, unsur secara melawan hukum, unsur melakukan perbuatan memperkaya diri sendiri atau orang lain atau suatu korporasi, unsur merugikan keuangan negara atau perekonomian negara, ketentuan Pasal 55 ayat (1) ke-1 KUHP dan ketentuan Pasal 64 ayat (1) KUHP.